Le projet de sol de la métropole montagne : Grenoble, de plaines en pentes - Charles Ambrosino; Jennifer Buyck (Revue de Géographie Alpine)
Mountains are both an intangible geomorphological condition of and a structuring identity marker for a good number of activities in the Grenoble region. And yet, they stand out because of their absence from metropolitan policies. Such an absence calls the Grenoble metropolis project and its cultural basis into question – all the more so because the ambition “to assert its status as a mountain metropolis” and “to rethink its relationship with the mountains and their slopes in all its aspects and specificities” is an objective that is clearly stated in the planning documents. A careful reading of these documents reveals that the image of the mountains, as used therein, has not escaped the concepts imposed by modernity: they are presented as a nature reserve to be preserved, an emblem to showcase and a recreational activity area surrendered to tourism. Beyond what can only be described as a functionalist vision of an Alpine city, that is, a view that considers the mountains merely as objects among many others, what urban planning activities have actually been rolled out? What do they tell us about the representations of this “mountain metropolis” under construction, its narrativisation and its goal? And more generally, what do they teach us about the direction that the processes are taking and about our conception of the landscape? We propose to answer these questions by making use of the work that has resulted from the many urban project workshops held at the Urban Planning and Alpine Geography Institute (IUGA), as well as the notion of “progetto di suolo” (land design project) that Italian urban planner Bernardo Secchi developed in the 1990s.